Productivity, markups, and trade: Evidence from Mexican manufacturing industries - Daniela Puggioni (Banco de México, 2019)
This paper applies a structural framework to estimate production function coefficients, obtain firm-level markup estimates, and evaluate the impact of the trade liberalization that took place in Mexico in the period 1984-1990 on the profitability of the firms operating in the domestic market and exporters. Quantitatively, the results show no evidence of substantial productivity growth, but some evidence of trade discipline on the price-cost margins. A markup premium is however identified for intensive exporters. Qualitatively, these results suggest that the effectiveness of trade policies crucially depends on adequately implementing complementary reforms aimed at improving the competitiveness and the efficiency in the allocation of resources in the internal market.
Keywords: D22; D24; F14; L11; L60; 330; Production function estimation; Productivity; Markups; Trade liberalization; Mexican manufacturing industries